Hijrah Thugs and Militanism: Study of the Anti-Usury Islamic Movement in the Surakarta - Warsito, Warsito; Wildan, Muhammad (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study confirms the inseparability of religious issues from the world. The migration of thugs to the Laskar is a matter of guidance and an opportunity to control resources. The phenomenon of Laskar legitimizing the termination of motor vehicle loans on the grounds of fighting usury and considering their actions correct has added to the study of the migration of former thugs. This phenomenon is studied using qualitative methods with a phenomenological approach. In-depth interviews took data from people involved in this activity. Data was also collected by observing sales activities or the behavior of buyers of bad credit motorbikes. Apart from that, researchers used documents from various books and journals that studied the migration of former thugs; the data was then analyzed using interactive techniques. This study shows that the authority of classical religion has diminished for former thugs, who have had the opportunity to directly access data from the internet and then draw their conclusions. This study also explains that economic factors have a significant role in changing a person's identity, so hijrah is not just a matter of guidance but economic control.